New insights into the seasonal diet of Antarctic krill using triacylglycerol and phospholipid fatty acids, and sterol composition - Ericson, JA; Hellessey, N; Peter Nichols; Stephen Nicol; So Kawaguchi; Hoem, N; Patti Virtue (2019)
Fatty acid analysis for estimating dietary sources in marine predators is a powerful tool in food web research. However, questions have been raised about using fatty acids as dietary indicators from whole lipid samples, rather than from separate lipid classes. A drawback of scientific field-based studies is that samples are rarely collected over extended periods, precluding seasonal dietary comparisons. We used fisheries samples obtained over one year to investigate seasonal variations in the fatty acid composition of separated phospholipids and triacylglycerols of Antarctic krill ( Euphausia superba ). Seasonal variation was observed in fatty acid biomarkers within triacylglycerol and phospholipid fractions of krill. Fatty acids in krill triacylglycerols (thought to best represent recent diet), reflected omnivorous feeding with highest percentages of flagellate biomarkers (18:4n-3) in summer, and diatom biomarkers (16:1n-7c) in autumn, winter and spring. Carnivory biomarkers (∑ 20:1 + 22:1 and 18:1n-9c/18:1n-7c) in krill were higher in autumn. Phospholipid fatty acids were less variable and higher in 20:5n-3 and 22:6n-3, which are essential components of cell membranes. Sterol composition did not yield detailed dietary information, but percentages and quantities of cholesterol, the major krill sterol, were significantly higher in winter and spring compared with summer and autumn. Copepod markers ∑ 20:1 + 22:1 were not strongly associated with the triacylglycerol fraction during some seasons, and neither was 18:4n-3. Krill might mobilise 18:4n-3 from triacylglycerols to phospholipids for conversion to long-chain (≥ C 20 ) polyunsaturated fatty acids, which would have implications for its role as a dietary biomarker. For the first time, we demonstrate the dynamic seasonal relationship between specific biomarkers and krill lipid classes.